OBSTACLES HINDERING THE IMPLEMENTATION OF STRATEGIC PLANNING FROM SECONDARY SCHOOL PRINCIPALS IN KHARTOUM STATE - Bannaga Taha Al-Zubair; El-Zain El-Khalefa El-khder (Managere: Indonesian Journal of Educational Management, 2021)
The study aimed at indemnifying the main obstacles that face the application strategic planning From Secondary School Principals in Khartoum State. For that purpose, the descriptive analytic method was used. The study population included all secondary school principals in Omdurman locality membrane 220. Out of the study population a random sample consisting of 120 principles was chosen. For the purpose of data collection, the researchers designed and used a questionnaire distributed to all sample members. To analyze the collected data, the statistical package (SPSS) was used. The main following results were reached: the school principals face difficulties in analyzed the point of the strength, weaken, opportunities, and threats facing their schools as they lack the basic scientific foundation and know ledge of strategic planning, The school principals encounter difficulties and problems when they handle and go about strategic planning of their schools due to the fact that they lack the basic required skills and competences regarding the implementation of the strategic planning processes. In view of the results being researched, it is recommended that: Obstacles that hinder the implementation of strategic planning need to be removed in order to active the school strategic planning processes.